2021
DOI: 10.3390/children8050393
|View full text |Cite
|
Sign up to set email alerts
|

Sunbed Use among 11- to 17-Year-Olds and Estimated Number of Commercial Sunbeds in England with Implications for a ‘Buy-Back’ Scheme

Abstract: Prior to 2011 legislation prohibiting children from using commercial sunbeds, the prevalence of sunbed use in 15- to 17-year-olds in some areas in England was as high as 50%. Despite significant decreases since 2011, children today still practice indoor tanning. We estimated current sunbed use in 11- to 17-year-olds in England, the number of available commercial sunbed units, and the associated cost of a ‘buy-back’ scheme to remove commercial sunbeds under a potential future policy to ban sunbeds. We undertook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Previous research has shown, however, that minors find loopholes to use tanning beds, despite a legal ban [ 35 , 36 , 37 , 38 , 39 ]. However, data from some countries also revealed that tanning bed use in minors has decreased over time since the implementation of the ban [ 35 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown, however, that minors find loopholes to use tanning beds, despite a legal ban [ 35 , 36 , 37 , 38 , 39 ]. However, data from some countries also revealed that tanning bed use in minors has decreased over time since the implementation of the ban [ 35 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown, however, that minors find loopholes to use tanning beds, despite a legal ban [ 35 , 36 , 37 , 38 , 39 ]. However, data from some countries also revealed that tanning bed use in minors has decreased over time since the implementation of the ban [ 35 , 40 , 41 ]. As we have seen in the US, several states allow commercial tanning bed use for minors when they have parental permission (consent or accompaniment).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the hypothetical scenario presented, all intervention costs were assigned to the public health campaign component of the intervention. An alternative use of resources would be to fund a ‘sunbed buy‐back’ scheme 7 to encourage commercial sunbed providers to repurpose their businesses. In a situation where an additional £10.97 million in intervention costs were available for this purpose, each provider in England could be paid £3709 per premise; 7 alongside the inclusion of a £1 million public health campaign (total intervention costs £11.97 million), this would remain a cost‐effective use of NHS resources.…”
Section: Discussionmentioning
confidence: 99%
“…Various strategies to reduce the harms associated with indoor tanning include increased taxation, public health campaigns and regulations restricting availability of commercial sunbeds 5 . Outright bans of commercial sunbeds have been introduced in Brazil, Australia and Iran 6 and there have been increasing calls from dermatological and oncological organizations to other jurisdictions, including populations that fall under the remit of the National Health Service (NHS) in England, to ban sunbeds 7–9 . Currently, commercial indoor tanning is legally available in the UK for those aged 18 years and older.…”
mentioning
confidence: 99%